Strategi Kantor Urusan Agama dalam Meningkatkan Pemahaman Masyarakat untuk Berwakaf ke Lembaga Wakaf Menuju Sertifikasi Tanah Wakaf (Studi Kasus di Nagari Parit Malintang Kecamatan Enam Lingkung Kabupaten Padang Pariaman) - Maysarah, Maysarah; Emrizal, Emrizal (IAIN Batusangkar, 2024)
The main problem in this research is what factors cause the lack of interest of the people of Nagari Parit Malintang to donate through waqf institutions and what strategies should be carried out by the Enam Lingkung District Religious Affairs Office (KUA) so that people register their waqf land according to applicable regulations. The purpose of this research is to find out what factors cause the lack of interest of the people of Nagari Parit Malintang to give waqf through waqf institutions and to find out what strategies the Enam Lingkung District Religious Affairs Office (KUA) must implement so that people register their waqf land according to applicable regulations. The type of research that the author uses is field research with a qualitative descriptive approach. The results of this research show that the factors causing the lack of interest of the people of Nagari Parit Malintang to give waqf through waqf institutions are economic factors, education level factors, and understanding factors about waqf. The people of Nagari Parit Malintang who are already waqf still lack knowledge and understanding regarding the procedures for implementing waqf registration through waqf institutions. The strategy carried out by the Enam Lingkung District KUA is to provide outreach to people who are already waqf and the procedures for making AIW and waqf land certification. The strategies they implemented have not been conveyed to the community well, and the KUA's strategy is still not efficient and effective regarding increasing the community's understanding of giving waqf through waqf institutions.